2014
DOI: 10.1364/ol.39.001593
|View full text |Cite
|
Sign up to set email alerts
|

Two-core transversally chirped microstructured optical fiber refractive index sensor

Abstract: We present a sensing architecture consisting of a two-core chirped microstructured optical fiber (MOF) for refractive index sensing of fluids. We show that by introducing a chirp in the hole size, the MOF can be a structure with decoupled cores, forming a Mach-Zehnder interferometer in which the analyte directly modulates the device transmittance by its differential influence on the effective refractive index of each core mode. We show that by filling all fiber holes with analyte, the sensing structure achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…For a small d max , the effective RI difference increases exponentially with n a as observed in Ref. 8. However, if d max is increased, it is observed that the effective RI difference has a completely different behavior and now decreases with n a (under current conditions we found that depends quadratically).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…For a small d max , the effective RI difference increases exponentially with n a as observed in Ref. 8. However, if d max is increased, it is observed that the effective RI difference has a completely different behavior and now decreases with n a (under current conditions we found that depends quadratically).…”
Section: Introductionsupporting
confidence: 81%
“…8 By using this novel concept, we designed a label-free biosensor by immobilization of an antigen sensor layer onto the walls of the air holes of rings surrounding one core of the fiber. 9 In this work, some refractometric features of dual-core chirped MOFs are evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Now, the refractive index of the layer of biomolecules directly modulates the device transmittance by its differential influence on the effective refractive index of each core mode, resulting in a variable phase difference between the optical path lengths of the interferometer arms. 9 Figure 2(a) shows the effective refractive index difference between the two fundamental modes that propagate through the fiber cores, Δn eff , as a function of wavelength. Although the difference between the two orthogonal polarizations is very small, the polarization state of the input beam may yields differences in the transmittance of the MOF, thus only the horizontal polarization is shown here.…”
Section: Resultsmentioning
confidence: 99%
“…The phase difference in Fig. 2(b) was approximated analytically by an exponential function, 9 which was then be used to derive the transmittance of the biosensor using the following expression:…”
Section: Resultsmentioning
confidence: 99%
“…Experiment result proved that the resolution of the proposed method is higher than that of the improved way, and the CLBG device keeps higher sensitivity with this method. [9]optimized parameters of concatenated structure in the method of simulated and discussed the influence that the lengths, periods and dc induced index changes of FBG and LPG and length of optical fiber between LPG and FBG has to influence reflection spectrum. Secondly, based on the optimized parameters for concatenated structure, such structures are fabricated and used to monitor concentration and temperature simultaneously.…”
Section: Introductionmentioning
confidence: 99%